Transmathematica 2019: The 2nd International Conference On Total Systems - Anderson, James A.D.W. (Transmathematica, 2019)
We describe the proceedings of Transmathematica 2019 - The 2nd International Conference on Total Systems which was held in Reading, UK on 1st July 2019. We describe how to cite Transmathematica journal papers and announce Transmathematica 2021 - The 3rd International Conference on Total Systems.